DYNAMICAL SYSTEM FOR COVID-19 OUTBREAK WITHIN VACCINATION TREATMENT - Sugiarto, Sigit; MA, Ratnah Kurniati; Nurwijaya, Sugian (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Covid-19 is a deadly infectious disease that occurs throughout the world. Therefore, it is necessary to prevent the transmission of Covid-19 such as vaccination. The purpose of this research is to modify the model of the spread of the Covid-19 disease from the previous model. The equilibrium points and the basic reproduction number ( ) of the modified model is determined. Then a stability analysis was carried out and a numerical simulation was carried out to see the dynamics of the population that occurred. The analysis performed on the model obtained two equilibriums, namely the disease-freeequilibrium and the endemic equilibrium. Disease-free equilibrium are locally asymptotically stable if . Meanwhile, the endemic equilibrium is locally asymptotically stable if . The numerical simulation results show the same results as the analytical results.